Fuzzy Logic Control for Balancing a Two-Armed Inverted Pendulum - EL Kinany, Boutaina; Mohamed Alfidi; Zakaria Chalh (Statistics, Optimization & Information Computing, 2023)
The unicycle robot is an activated model with only one wheel, which ensures its safety. Researchers were particularly interested in the unicycle robot because of its great robustness, which allows it to travel around without colliding with the ground. The inverted pendulum having two arms is modelled using a mathematical representation based on the Lagrangian formulation in this work, which embodies our concept of the unicycle robot. The fuzzy logic control algorithm will then be used to produce a high level of solidity for this system.